2017
DOI: 10.1111/1365-2478.12505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fracture fill on frequency‐dependent anisotropy of fractured porous rocks

Abstract: In fractured reservoirs, seismic wave velocity and amplitude depend on frequency and incidence angle. Frequency dependence is believed to be principally caused by the wave‐induced flow of pore fluid at the mesoscopic scale. In recent years, two particular phenomena, i.e., patchy saturation and flow between fractures and pores, have been identified as significant mechanisms of wave‐induced flow. However, these two phenomena are studied separately. Recently, a unified model has been proposed for a porous rock wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
(109 reference statements)
0
13
0
2
Order By: Relevance
“…The properties of the pore fluids and their mobility through the porous media complicate the distinction between pore fluid distribution and rock fabric in fractured media. Kong et al (2017) remarked that the fracture‐filling fluid can disguise P wave dispersion and attenuation effects due to fracture orientation, when its modulus is much smaller than that of the pore‐filling fluid. Amalokwu et al (2015) found that fractures obliquely oriented with respect to wave propagation can lead to S wave velocity anisotropy (SWVA) drop with increasing water saturation, because V S 2 (sensitive to fluid compressibility reduction) decreases, while V S 1 , considered independent of the pore fluid (Tillotson et al, 2012), remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of the pore fluids and their mobility through the porous media complicate the distinction between pore fluid distribution and rock fabric in fractured media. Kong et al (2017) remarked that the fracture‐filling fluid can disguise P wave dispersion and attenuation effects due to fracture orientation, when its modulus is much smaller than that of the pore‐filling fluid. Amalokwu et al (2015) found that fractures obliquely oriented with respect to wave propagation can lead to S wave velocity anisotropy (SWVA) drop with increasing water saturation, because V S 2 (sensitive to fluid compressibility reduction) decreases, while V S 1 , considered independent of the pore fluid (Tillotson et al, 2012), remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…We would get the opposite result if we adjust the aforementioned parameters in a way that renders the fractures stiffer. Concerning the properties of the pore fluid, Kong et al (2017) showed that, when the fractures are saturated with a very compressible fluid, such as gas, and the background rock is fully saturated with water, seismic attenuation may also be important. Although the analytical derivation presented in our work could be used to study the discrepancies between the TLM and LST approaches in such context, the corresponding analysis is beyond the scope of this paper and will be the subject of future work.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Plenty of rock physics theories that have been derived specifically to explore the frequency dependence in the elastic stiffness tensors press the main challenges in carrying out seismic AVO modeling analysis, principally porosity-anisotropic velocity transform, velocity-pressure relation, fluid saturation and velocity prediction. In this study, an extended poroelastic theory based on Carcione et al (2013) and Kong et al (2017) was utilized for the determination of frequency-dependent full elastic stiffness tensors. Additionally, the introduced theory allows us to account for fluid-sensitive attenuation and velocity dispersion attributes in the frame of anisotropic viscoelasticity.…”
Section: Anisotropic Wave Attenuation and Velocity Dispersion In A Fluid-saturated Fractured Poroelastic Mediummentioning
confidence: 99%
“…where i indicates either the P-, the SV-or the SH-wave mode. Precise forms of the above relationships are also presented in Kong et al (2017) and He et al (2020).…”
Section: Anisotropic Wave Attenuation and Velocity Dispersion In A Fluid-saturated Fractured Poroelastic Mediummentioning
confidence: 99%
See 1 more Smart Citation